Students’ perspectives on social media-based learning of writing through Instagram - Renata Kenanga Rinda; Adriadi Novawan; Alfi Hidayatu Miqawati (Journal of English in Academic and Professional Communication, 2018)
Teaching writing in an EFL classroom is generally accepted as a composite task. Time-consuming process with various steps is required to train the students to be able to produce successful essays. Many methods and approaches including traditional and modern ways have been practiced by teachers. However, there has been little study devoted to confirm its effectiveness, particularly that of technology-enhanced pedagogy. To fill this gap, this paper presents the results of a case study which investigated the perspective of students who participated in a technology-based writing class about their experience when joining the writing course which mainly employed Instagram. Close ended questionnaire and focus group discussion were used to collect the data. Based on the data analysis, the students’ perspectives indicate that: 1) they believed that their peers’ feedback on Instagram help them to correct grammar , 2) particular posts on Instagram  help them learn new vocabularies and find better ideas to construct writing, 2) Instagram enhanced spelling correction, 3) students believed that negative comments and over-corrected feedback on Instagram make them not only feel under pressure but also become motivated to write a better essay, 4) ads in Instagram distracted their focus when writing, and 5) bad internet connection impeded the process of writing on Instagram. Finally, to maximize its strengths and minimized its weaknesses, it is suggested that students’ interaction, students’ knowledge of technology, teacher’s role, and accessible internet provided by the institution must be augmented.   Keywords: writing, social media-based learning, Instagram, students’ perception